PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN PENGUSAHA KENA PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA KENDARI - Djumiati, Waode Sitti (JURNAL AKUNTANSI, 2016)
Tax Office Primary Kendari was established with the goal of improving taxpayer compliance / taxable employers in meeting their tax obligations so as to increase state revenue. One of the efforts to achieve its objectives, Tax Office Primary Kendari always making changes to the tax administration system. Factor that may affect the level of compliance of employers taxable one of which is to modernize the tax administration system. This study aimed to see whether or not the effect of taxation on the modernization variable rate taxable employer complianceat Tax Office Primary Kendari.The population of this research is all taxable employers listed on the Tax Office Primary Kendari. Samples were taken by using a method Convenience Sampling that was taken 40 taxable employers sampled. This study uses regression analysis to determine the effect of independent variables, namely the modernization of the tax administration system.The results showed that significant test of individual parameters (t test) showed that the modernization of the tax administration system variables significant positive effect on the level of compliance of employers taxable at Tax Office Primary Kendari. Keywords: level of compliance, the modernization of the tax administration system.